Calcul intégral - Faraut, Jacques, 1940- (Collection Enseignement sup. Mathématiques., 2006)
This work deals with integrals in calculus which is a fundamental tool for mathematical analysis and for the calculation of probabilities. The work is divided into 11 chapters as follows: Computations using integrals, for example Lebesgue integration techniques as it applies to measurable real analysis, measurable spaces, for example Euclidean n-space, integrable functions defined on Rn, the calculations of Lebesgue-Stieltjes integration, their functions as defined by integrals, convolution, Fourier transform, Fourier series, the applications and their complements.